Composite positive electrode material and preparation method and application thereof

By introducing carbon nanotubes and amorphous manganese-based oxide nanoparticles into manganese-based positive electrode materials, building a conductive network, the instability and low conductivity of manganese-based positive electrode materials are solved, and the cycling performance of the battery is significantly improved and Rate performance.

CN119419244AActive Publication Date: 2025-02-11SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411540682.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The manganese-based positive electrode material is unstable in aqueous solution, has poor cycle stability, slow ion insertion and diffusion kinetics, and low conductivity leads to low Coulomb efficiency and rate performance.

Method used

Using composite positive electrode materials, including carbon nanotubes and amorphous manganese-based oxide nanoparticles located on the surface of the carbon nanotube, the uniform growth and fixation of nanoparticles are achieved through microwave heat treatment and calcination treatment to build a conductive network.

Benefits of technology

It improves the solid-state diffusion kinetics of zinc ions, buffers volume changes caused by the ion insertion/detachment process, reduces the collapse of the electrode material structure, and significantly improves the cycling, rate performance and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419244A_ABST
    Figure CN119419244A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a composite positive electrode material and a preparation method and application thereof. The composite positive electrode material comprises a carbon nanotube and amorphous manganese-based oxide nanoparticles located on the surface of the carbon nanotube, the chemical general formula of the amorphous manganese-based oxide nanoparticles is (NiO) x (MnO) y, 0.25 < = x < = 0.75, 0.25 < = y < = 0.75, and x + y = 1. According to the composite positive electrode material disclosed by the invention, the amorphous manganese-based oxide is uniformly coated on the surface of the carbon nanotube, so that the composite positive electrode material has excellent cycle life and specific discharge capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a composite positive electrode material and a preparation method and application thereof. Background Art

[0002] At present, the development of renewable energy represented by solar energy and wind energy is crucial to scientific development. However, the intermittent nature and geographical limitations of renewable energy make it impossible for them to completely replace traditional fossil fuels. These problems have promoted the rapid development of new energy storage technologies. Lithium-ion batteries (LIBs) occupy most of the energy storage market due to their excellent electrochemical properties. However, problems such as the high price and flammability of organic electrolytes and the increasing shortage of lithium resources have restricted their further development. In recent years, aqueous zinc-ion batteries (ZIBs) have attracted much attention in the field of energy storage due to their inherent advantages. The zinc anode used in ZIBs has a high theoretical capacity (820mAh·g -1 ), low redox potential (-0.763Vvs.SHE) and abundant reserves. In addition, aqueous electrolytes have higher ionic conductivity than organic electrolytes and are cheaper and safer. Therefore, ZIBs are considered to have great development and application space in the next generation of large-scale energy storage devices.

[0003] The cathode material plays a decisive role in the electrochemical performance of ZIBs. So far, the cathode materials that have been widely reported mainly include vanadium-based materials, manganese-based materials and Prussian blue analogs. Among them, manganese-based materials have received widespread attention due to their unique advantages. First, manganese (Mn) has a variety of valence states (Mn 2+ , Mn 3 +、Mn 4+ , Mn 7+ ), so manganese-based compounds have obvious atomic structure diversity and multivalent phases. At the same time, manganese reserves are abundant and low in cost. In addition, manganese-based compounds are safe, non-toxic and environmentally friendly. Therefore, manganese-based compounds have become one of the most promising candidates for the positive electrode of zinc-ion batteries.

[0004] Although manganese-based cathode materials have good performance, some key issues limit the further development of manganese-based materials. First, the solubility and disproportionation reaction of manganese-based materials make them unstable in aqueous solution, which leads to poor cycle stability. 2+ The high charge density and Zn 2+ With [MnO 6 ] leads to slow ion insertion and diffusion kinetics. In addition, the inherent low conductivity of manganese-based materials leads to insufficient charge transfer kinetics, which in turn reduces their coulombic efficiency and rate performance.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] An object of the present invention is to provide a composite positive electrode material to overcome the shortcomings of the above-mentioned manganese-based positive electrode material and have excellent cycle life and discharge specific capacity.

[0007] Another object of the present invention is to provide a method for preparing the composite positive electrode material, which is simple and easy to implement, environmentally friendly, and has mild and controllable conditions.

[0008] Another object of the present invention is to provide a positive electrode sheet as described above.

[0009] Another object of the present invention is to provide a battery as described above.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0011] A composite positive electrode material comprises carbon nanotubes and amorphous manganese-based oxide nanoparticles located on the surface of the carbon nanotubes, wherein the chemical formula of the amorphous manganese-based oxide nanoparticles is (NiO) x (MnO) y , 0.25≤x≤0.75, 0.25≤y≤0.75, and x+y=1.

[0012] In some embodiments, the amorphous manganese-based oxide nanoparticles include (NiO) 0.5 (MnO) 0.5 、(NiO) 0.75 (MnO) 0.25 and (NiO) 0.25 (MnO) 0.75 At least one of .

[0013] In some embodiments, the average particle size of the amorphous manganese-based oxide nanoparticles is 6 to 12 nm.

[0014] In some embodiments, the mass content of the amorphous manganese-based oxide nanoparticles in the composite positive electrode material is 70% to 90%.

[0015] A method for preparing a composite positive electrode material comprises the following steps:

[0016] A first mixed system of a manganese source, a nickel source, an organic solvent and a chelating agent is mixed with carbon nanotubes to obtain a second mixed system, the second mixed system is subjected to microwave heat treatment, solid-liquid separation is performed, and solids are collected and calcined.

[0017] In some embodiments, the manganese source includes manganese acetate and / or manganese acetylacetonate.

[0018] In some embodiments, the nickel source includes nickel acetate and / or nickel acetylacetonate.

[0019] In some embodiments, the organic solvent comprises benzyl alcohol.

[0020] In some embodiments, the chelating agent includes 1,3-propylene glycol.

[0021] In some embodiments, the molar ratio of the manganese source to the nickel source is (0.5-2):1.

[0022] In some embodiments, in the first mixed system, the concentration of the manganese source is 50 to 150 mmol / L, and the concentration of the nickel source is 50 to 150 mmol / L.

[0023] In some embodiments, the volume ratio of the organic solvent to the chelating agent is (4-19):1.

[0024] In some embodiments, the method for preparing the first mixed system specifically comprises: mixing a manganese source, a nickel source, an organic solvent and a chelating agent and stirring for 10 to 20 minutes.

[0025] In some embodiments, in the second mixed system, the concentration of the carbon nanotubes is 1 to 4 mg / mL.

[0026] In some embodiments, the temperature of the microwave heat treatment is 150-210° C., and the time of the microwave heat treatment is 5-40 min.

[0027] In some embodiments, during the microwave heat treatment, the second mixed system is stirred at a speed of 300 to 900 rpm.

[0028] In some embodiments, the calcination temperature is 160-240° C., and the calcination time is 1-3 hours.

[0029] In some embodiments, the calcination process is carried out in an atmosphere of protective gas.

[0030] In some embodiments, before the calcination, the solid is dried at a temperature of 60 to 90° C. for a time of 5 to 10 hours.

[0031] A positive electrode sheet comprises the composite positive electrode material or the composite positive electrode material prepared by the method for preparing the composite positive electrode material.

[0032] A battery comprises the positive electrode sheet.

[0033] An electrical device comprises the battery.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] (1) The composite positive electrode material of the present invention has abundant vacancies and reaction sites in the amorphous manganese-based oxide structure, thereby providing more ion transport channels, shortening the ion diffusion distance, and effectively promoting the solid-state diffusion kinetics of zinc ions. The amorphous manganese-based oxide can effectively buffer the volume change caused by the ion insertion / extraction process, reduce the collapse of the electrode material structure, and improve the cycle performance of the battery; the amorphous manganese-based oxide is uniformly coated on the surface of the carbon nanotube to form a composite positive electrode material, and by introducing the conductive medium carbon nanotube, a "amorphous manganese-based oxide nanoparticle / conductive medium" conductive network is constructed. Since the carbon nanotube has super strong conductivity, it can improve the low conductivity of the manganese-based oxide. At the same time, the strong interface interaction between the manganese oxide nanoparticles and CNTs can fix the nanoparticles, prevent agglomeration, alleviate structural collapse, and improve the cycle life of the composite positive electrode material.

[0036] (2) The preparation method of the composite positive electrode material of the present invention can achieve confined growth based on the combination of organic solvent and chelating agent. By introducing conductive medium carbon nanotubes and using microwave heat treatment, amorphous manganese-based oxide nanoparticles are induced to grow uniformly in the conductive network, thereby realizing the controllable synthesis of the composite positive electrode material. The method has a mild reaction, and the reaction products are precisely controllable. The microwave synthesis method has a fast reaction rate and a short time consumption, and has the potential for large-scale production. The reaction raw materials are safe, low-toxic and low-pollution.

[0037] (3) The battery of the present invention has excellent cycle performance, rate performance and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0039] Figure 1 X-ray diffraction patterns (XRD) of the composite positive electrode material in Example 2 of the present invention and the composite positive electrode material in Comparative Example 1;

[0040] Figure 2 This is a transmission electron microscope image (TEM) of the composite positive electrode material in Example 2 of the present invention;

[0041] Figure 3The AC impedance spectra of the composite positive electrode material in Example 2 of the present invention and the composite positive electrode material in Comparative Example 1 are shown. DETAILED DESCRIPTION

[0042] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0043] A composite positive electrode material includes carbon nanotubes (CNTs) and amorphous manganese-based oxide nanoparticles located on the surface of the carbon nanotubes. The chemical formula of the amorphous manganese-based oxide nanoparticles is (NiO) x (MnO) y , 0.25≤x≤0.75, 0.25≤y≤0.75, and x+y=1.

[0044] The composite positive electrode material of the present invention has abundant vacancies and reaction sites in the amorphous manganese-based oxide structure, thereby providing more ion transport channels, shortening the ion diffusion distance, and effectively promoting the solid-state diffusion kinetics of zinc ions. More importantly, the amorphous manganese-based oxide can effectively buffer the volume change caused by the ion insertion / extraction process, reduce the collapse of the electrode material structure, and significantly improve the cycle performance of the battery; the amorphous manganese-based oxide is uniformly coated on the surface of the carbon nanotube, and the conductive medium carbon nanotube is introduced to construct an "amorphous manganese-based oxide nanoparticle / conductive medium" conductive network. Since CNTs have super strong conductivity, the low conductivity of manganese-based oxide can be improved. At the same time, the strong interface interaction between manganese oxide nanoparticles and CNTs can fix the nanoparticles, prevent agglomeration, alleviate structural collapse, and improve the cycle life of the composite positive electrode material.

[0045] In some embodiments, x is 0.25, 0.3, 0.4, 0.5, 0.6, 0.7 or 0.75, etc., and y is 0.25, 0.3, 0.4, 0.5, 0.6, 0.7 or 0.75, etc.

[0046] In some embodiments, the amorphous manganese-based oxide comprises (NiO) 0.5 (MnO) 0.5 、(NiO) 0.75 (MnO) 0.25 and (NiO) 0.25 (MnO) 0.75 At least one of .

[0047] In some embodiments, the average particle size of the amorphous manganese-based oxide is 6-12 nm, such as 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm or 12 nm, etc. The amorphous manganese-based oxide of the present invention has a suitable average particle size and grows uniformly along the surface of CNTs.

[0048] In some embodiments, the mass content of amorphous manganese-based oxide nanoparticles in the composite positive electrode material is 70% to 90%, for example 70%, 75%, 80%, 85% or 90%. Amorphous manganese-based oxide nanoparticles having a suitable proportion in the composite positive electrode material is more conducive to improving the electrochemical performance of the positive electrode material.

[0049] According to another aspect of the present invention, the present invention also relates to a method for preparing a composite positive electrode material, comprising the following steps:

[0050] A first mixed system of a manganese source, a nickel source, an organic solvent and a chelating agent is mixed with carbon nanotubes to obtain a second mixed system, the second mixed system is subjected to microwave heat treatment, solid-liquid separation is performed, and solids are collected and calcined.

[0051] The preparation method of the composite positive electrode material of the present invention can realize the confined growth effect based on the combination of organic solvent and chelating agent. By introducing conductive medium carbon nanotubes and adopting microwave heat treatment, amorphous manganese-based oxide nanoparticles are induced to grow uniformly in the conductive network, thereby realizing the controllable synthesis of the composite positive electrode material.

[0052] In some embodiments, the manganese source includes manganese acetate and / or manganese acetylacetonate.

[0053] In some embodiments, the nickel source includes nickel acetate and / or nickel acetylacetonate.

[0054] In some embodiments, the organic solvent includes benzyl alcohol.

[0055] In some embodiments, the chelating agent includes 1,3-propylene glycol.

[0056] In some embodiments, the manganese source and the nickel source of the present invention adopt a suitable molar ratio, and the molar ratio of the manganese source to the nickel source is (0.5-2):1. For example, 0.5:1, 0.6:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.8:1 or 2:1.

[0057] In some embodiments, in the first mixed system, the concentration of the manganese source is 50-150 mmol / L, such as 50 mmol / L, 60 mmol / L, 80 mmol / L, 100 mmol / L, 120 mmol / L, 130 mmol / L, 150 mmol / L, etc. The concentration of the nickel source is 50-150 mmol / L, such as 50 mmol / L, 60 mmol / L, 80 mmol / L, 100 mmol / L, 120 mmol / L, 130 mmol / L, 150 mmol / L, etc. The manganese source and the nickel source have appropriate concentrations to ensure subsequent reactions, which is conducive to the generation of amorphous manganese-based oxide nanoparticles of appropriate particle size.

[0058] In some embodiments, the volume ratio of the organic solvent to the chelating agent is (4-19):1, such as 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 15:1, 17:1 or 19:1, etc. In some embodiments, the organic solvent and the chelating agent are in a suitable volume ratio, which is more conducive to ensuring that the two cooperate to play a confining role, so as to obtain amorphous manganese-based oxide nanoparticles of suitable particle size.

[0059] In some embodiments, the preparation method of the first mixed system specifically includes: mixing and stirring the manganese source, the nickel source, the solvent and the chelating agent for 10 to 20 minutes, for example, 10 minutes, 11 minutes, 12 minutes, 15 minutes, 16 minutes, 18 minutes, 20 minutes, etc. The present invention adopts a suitable mixing and stirring time to fully mix and dissolve the raw materials.

[0060] In some embodiments, in the second mixed system, the concentration of carbon nanotubes is 1 to 4 mg / mL, such as 1 mg / mL, 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3 mg / mL, 3.5 mg / mL or 4 mg / mL. The carbon nanotubes in the second mixed system have a suitable concentration, which is more conducive to the growth of amorphous manganese-based oxide nanoparticles on their surface, thereby improving the comprehensive electrochemical performance of the composite positive electrode material. If the amount of carbon nanotubes added is too low, the conductivity of the composite material will not be significantly improved; if the amount of carbon nanotubes added is too high, the proportion of active substances in the composite positive electrode material is low, resulting in a decrease in the specific capacity of the material.

[0061] In some embodiments, the temperature of microwave heat treatment is 150-210°C, such as 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, etc., or any range between the two. The time of microwave heat treatment is 5-40min, such as 5min, 10min, 15min, 20min, 25min, 30min or 40min, etc. In some embodiments, during the microwave heat treatment, the second mixed system is stirred, and the stirring speed is 300-900rpm, such as 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm, 900rpm, etc. Microwave heat treatment uses a microwave reactor, which is equipped with a magnetic stirring device inside. The purpose of stirring includes: making the reaction liquid heated evenly during the reaction process. The present invention, through the cooperation of the above-mentioned microwave heat treatment conditions, has mild reaction conditions, accurately controllable reaction products, fast reaction rate, and fully reacts the materials to grow uniform amorphous manganese-based oxide nanoparticles on the surface of carbon nanotubes. If the temperature of the microwave reaction is too low or the reaction time is too short, the reaction will be incomplete, resulting in a decrease in product yield; if the temperature of the microwave reaction is too high or the reaction time is too long, the reaction will be excessive, resulting in crystallization of nanoparticles.

[0062] In some embodiments, the solid-liquid separation is performed by centrifugal solid-liquid separation, and the solid after the solid-liquid separation is washed, and the washing agent includes ether.

[0063] In some embodiments, the calcination temperature is 160-240°C, such as 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, etc., and the calcination time is 1-3h, such as 1h, 1.5h, 2h, 2.5h, 3h, etc. The calcination atmosphere is a protective gas, such as argon. The present invention adopts low-temperature calcination to remove organic groups in the product and enhance the conductivity of the material. The calcination temperature and time of the present invention are suitable, which is more conducive to ensuring that the composite positive electrode material has high capacity and excellent cyclability; if the calcination temperature is too low and the calcination time is too short, the organic groups will not be removed cleanly; if the calcination temperature is too high and the calcination time is too long, the amorphous nanoparticles will be recrystallized and the amorphous structure will be destroyed.

[0064] In some embodiments, before the calcination, the solid is dried at a temperature of 60 to 90° C., such as 60° C., 70° C., 80° C., 90° C., etc. The drying time is 5 to 10 hours, such as 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours, etc.

[0065] According to another aspect of the present invention, the present invention relates to a positive electrode sheet, comprising the composite positive electrode material, or the composite positive electrode material prepared by the method for preparing the composite positive electrode material.

[0066] The positive electrode sheet of the present invention comprises a positive electrode current collector and a positive electrode material layer arranged on at least one side surface of the positive electrode current collector, wherein the positive electrode material layer contains the composite positive electrode material, a conductive agent and a binder.

[0067] According to another aspect of the present invention, the present invention relates to a battery comprising the above-mentioned positive electrode sheet.

[0068] The battery of the present invention has excellent cycle performance, rate performance and safety performance.

[0069] In some embodiments, the battery comprises a zinc ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte.

[0070] According to another aspect of the present invention, the present invention relates to an electric device comprising the above-mentioned battery, and the electric device includes an electric car and the like.

[0071] The following is further explained in conjunction with specific embodiments and comparative examples.

[0072] Example 1

[0073] A method for preparing a composite positive electrode material comprises the following steps:

[0074] (1) Weigh 0.375 mmol of manganese acetate and 0.375 mmol of nickel acetate and transfer them to a 10 mL microwave reaction tube. Weigh 4.75 mL of anhydrous benzyl alcohol and 0.25 mL of 1,3-propylene glycol and transfer them to a microwave reaction tube, and stir for 15 min until the solid powder is completely dissolved in the mixed solution of benzyl alcohol and 1,3-propylene glycol to obtain a first mixed system.

[0075] (2) 14 mg of carbon nanotubes were added to the first mixed system for the first time, and the mixture was stirred evenly to form a stable second mixed system.

[0076] (3) Insert the microwave reaction tube into the inner cavity of the microwave reactor, set the parameters of the microwave reactor as follows: maximum temperature of 160° C., heating time of 30 min, rotation speed of 600 rpm, and perform microwave heat treatment on the second mixed system.

[0077] (4) The product after microwave heat treatment reaction was centrifuged, the precipitate was taken, washed with ether for 3 times, and dried in an oven at 80°C for 8 hours to obtain the primary product. The primary product was calcined in a tubular furnace under argon atmosphere, heated to 200°C at a heating rate of 3°C / min and kept at a constant temperature for 2 hours, and then cooled naturally to obtain an amorphous state (NiO) 0.5 (MnO) 0.5 / CNTs composite positive electrode materials.

[0078] Example 2

[0079] A method for preparing a composite positive electrode material comprises the following steps:

[0080] (1) Weigh 0.375 mmol of manganese acetate and 0.375 mmol of nickel acetate and transfer them to a 10 mL microwave reaction tube. Weigh 4.5 mL of anhydrous benzyl alcohol and 0.5 mL of 1,3-propylene glycol and transfer them to a microwave reaction tube, and stir for 15 min until the solid powder is completely dissolved in the benzyl alcohol and 1,3-propylene glycol mixture to obtain a first mixed system.

[0081] (2) Add 14 mg of carbon nanotubes to the first mixed system and stir evenly to form a stable second mixed system.

[0082] (3) Insert the microwave reaction tube into the inner cavity of the microwave reactor, set the parameters of the microwave reactor as follows: maximum temperature of 160° C., heating time of 30 min, rotation speed of 600 rpm, and perform microwave heat treatment on the second mixed system.

[0083] (4) The product after microwave heat treatment reaction was centrifuged, the precipitate was taken, washed with ether for 3 times, and finally dried in an oven at 80°C for 8 hours to obtain the primary product. The primary product was calcined in a tubular furnace under argon atmosphere, heated to 200°C at a heating rate of 3°C / min and kept at a constant temperature for 2 hours, and then cooled naturally to obtain an amorphous state (NiO) 0.5 (MnO) 0.5 / CNTs composite positive electrode materials.

[0084] Example 3

[0085] A method for preparing a composite positive electrode material comprises the following steps:

[0086] (1) Weigh 0.375 mmol of manganese acetate and 0.375 mmol of nickel acetate and transfer them to a 10 mL microwave reaction tube. Weigh 4.25 mL of anhydrous benzyl alcohol and 0.75 mL of 1,3-propylene glycol and transfer them to a microwave reaction tube, and stir for 15 min until the solid powder is completely dissolved in the mixture of benzyl alcohol and 1,3-propylene glycol to obtain a first mixed system.

[0087] (2) Add 14 mg of carbon nanotubes to the first mixed system and stir evenly to form a stable second mixed system.

[0088] (3) Insert the microwave reaction tube into the inner cavity of the microwave reactor, set the parameters of the microwave reactor as follows: maximum temperature of 160° C., heating time of 30 min, and rotation speed of 600 rpm, and perform microwave heat treatment on the second mixed system.

[0089] (4) The product after microwave heat treatment reaction was centrifuged to obtain a precipitate, washed with ether three times, and finally dried in an oven at 80°C for 8 hours to obtain a primary product. The primary product was calcined in a tubular furnace under an argon atmosphere, heated to 200°C at a heating rate of 3°C / min and kept at a constant temperature for 2 hours, and then cooled naturally to obtain an amorphous state (NiO) 0.5 (MnO) 0.5 / CNTs composite positive electrode materials.

[0090] Example 4

[0091] A method for preparing a composite positive electrode material, which differs from Example 2 in that:

[0092] In step (2), 5 mg of carbon nanotubes are added to the first mixed system and stirred evenly to form a stable second mixed system.

[0093] Example 5

[0094] A method for preparing a composite positive electrode material, which differs from Example 2 in that:

[0095] In step (2), 20 mg of carbon nanotubes are added to the first mixed system and stirred evenly to form a stable second mixed system.

[0096] Example 6

[0097] A method for preparing a composite positive electrode material, which differs from Example 2 in that:

[0098] In step (3), the microwave reaction tube is inserted into the inner cavity of the microwave reactor, and the parameters of the microwave reactor are set as follows: the maximum temperature is 150° C. and the heating time is 5 min.

[0099] Example 7

[0100] A method for preparing a composite positive electrode material, which differs from Example 2 in that:

[0101] In step (3), the microwave reaction tube is inserted into the inner cavity of the microwave reactor, and the parameters of the microwave reactor are set as follows: the maximum temperature is 210° C., and the heating time is 40 min.

[0102] Example 8

[0103] A method for preparing a composite positive electrode material, which differs from Example 2 in that:

[0104] In step (4), the mixture is heated to 160° C. at a heating rate of 3° C. / min and maintained at this temperature for 1 h.

[0105] Example 9

[0106] A method for preparing a composite positive electrode material, which differs from Example 2 in that:

[0107] In step (4), the mixture is heated to 240° C. at a heating rate of 3° C. / min and maintained at a constant temperature for 3 h.

[0108] Comparative Example 1

[0109] A method for preparing a composite positive electrode material comprises the following steps:

[0110] (1) Weigh 0.375 mmol of manganese acetate and 0.375 mmol of nickel acetate and transfer them to a 10 mL microwave reaction tube. Weigh 5 mL of anhydrous benzyl alcohol and transfer them to the microwave reaction tube. Stir for 15 min until the solid powder is completely dissolved in the benzyl alcohol.

[0111] (2) Add 14 mg of carbon nanotubes and stir evenly to form a stable dispersion.

[0112] (3) Insert the microwave reaction tube into the cavity of the microwave reactor, and set the parameters of the microwave reactor as follows: the maximum temperature is 160°C, the heating time is 30 min, and the speed is 600 rpm. The product after the reaction is centrifuged to obtain the precipitate, washed with ether three times, and finally dried in an oven at 80°C for 8 h to obtain the initial product. The initial product is calcined at high temperature in a tubular furnace under argon atmosphere, heated to 200°C at a heating rate of 3°C / min and kept at a constant temperature for 2 h, and then cooled naturally to obtain crystalline (NiO) 0.5 (MnO) 0.5 / CNTs composite positive electrode materials.

[0113] Experimental example

[0114] 1. XRD and TEM images of composite cathode materials

[0115] The XRD patterns of the composite positive electrode material in Example 2 of the present invention and the composite positive electrode material in Comparative Example 1 are as follows: Figure 1 As shown, it can be seen that the diffraction peaks at 36.5°, 42°, 61°, 73° and 77° in the XRD spectrum of the composite positive electrode material of Comparative Example 1 correspond to the metal oxide (NiO) 0.5 (MnO) 0.5 , the diffraction peak indicated by the heart-shaped icon at 24° corresponds to carbon nanotubes. In contrast, the XRD pattern of Example 2 has no obvious diffraction peaks. This is because the introduction of the chelating agent 1,3-propylene glycol triggers the confinement effect, inhibits the growth of metal oxide nanoparticles, and forms an amorphous state (NiO) 0.5 (MnO) 0.5 / CNTs composite positive electrode materials.

[0116] The TEM image of the composite positive electrode material in Example 2 of the present invention is as follows Figure 2As shown, it can be seen that the average particle size of the amorphous manganese-based oxide nanoparticles is 10 nm, and the nanoparticles grow uniformly along the surface of CNTs.

[0117] 2. Battery electrochemical performance test

[0118] The composite positive electrode materials of each embodiment and comparative example are respectively prepared into zinc ion batteries, comprising the following steps:

[0119] (1) Preparation of positive electrode sheet: Disperse polyvinylidene fluoride, conductive carbon black, and composite positive electrode material in an appropriate amount of N-methylpyrrolidone at a mass ratio of 7:2:1, stir evenly to form a slurry of appropriate consistency, apply it on a 10μm commercial titanium foil, and vacuum dry to obtain a positive electrode sheet. The positive electrode sheet is punched into a round sheet with a diameter of 12mm and directly used as the positive electrode of the zinc ion battery. The active material loading is about 1mg / cm 2 .

[0120] (2) Preparation of negative electrode sheet: After wiping clean the 80 μm commercial zinc foil with anhydrous ethanol, it was punched into a circular sheet with a diameter of 16 mm and directly used as the negative electrode of the zinc ion battery.

[0121] (3) Preparation of electrolyte: Using zinc sulfate heptahydrate as the solute and deionized water as the solvent, a 2 mol / L zinc sulfate solution was prepared and directly used for zinc ion battery electrolyte.

[0122] (4) Assemble the zinc ion battery in the order of negative electrode shell-negative electrode sheet-diaphragm-electrolyte-positive electrode sheet-gasket-spring-positive electrode shell. The amount of electrolyte used is 150 mL, the battery shell model is CR2032, and the diaphragm model is glass fiber diaphragm (GF / D).

[0123] At current densities of 1 A / g and 2 A / g, the electrochemical performance of the batteries of each embodiment and comparative example was tested, and the test results are shown in Table 1. The AC impedance spectra of the composite positive electrode material in Example 2 and the composite positive electrode material in Comparative Example 1 are shown in Table 1. Figure 3 shown.

[0124] Table 1 Electrochemical performance test results of the battery

[0125]

[0126]

[0127] As shown in Table 1, the battery obtained by the composite positive electrode material of the present invention has excellent electrochemical performance, and the cycle capacity retention rate of 500 cycles can reach 72.7%, and the cycle capacity retention rate of 1000 cycles can reach 75.4%. In Comparative Example 1, no 1,3-propylene glycol was added, and the cycle capacity retention rate of the battery prepared by the obtained crystalline composite positive electrode material was significantly reduced.

[0128] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite positive electrode material, characterized in that: The invention comprises carbon nanotubes and amorphous manganese-based oxide nanoparticles located on the surface of the carbon nanotubes, wherein the chemical formula of the amorphous manganese-based oxide nanoparticles is (NiO) x (MnO) y , 0.25≤x≤0.75, 0.25≤y≤0.75, and x+y=1.

2. The composite positive electrode material according to claim 1, characterized in that The amorphous manganese-based oxide nanoparticles include (NiO) 0.5 (MnO) 0.5 、(NiO) 0.75 (MnO) 0.25 and (NiO) 0.25 (MnO) 0.75 At least one of; and / or, the average particle size of the amorphous manganese-based oxide nanoparticles is 6 to 12 nm; And / or, the mass content of the amorphous manganese-based oxide nanoparticles in the composite positive electrode material is 70% to 90%.

3. A method for preparing a composite positive electrode material, characterized in that: The following steps are involved: A first mixed system of a manganese source, a nickel source, an organic solvent and a chelating agent is mixed with carbon nanotubes to obtain a second mixed system, the second mixed system is subjected to microwave heat treatment, solid-liquid separation is performed, and solids are collected and calcined.

4. The method for preparing a composite positive electrode material according to claim 3, characterized in that: Contains at least one of the following features (1) to (8): (1) The manganese source includes manganese acetate and / or manganese acetylacetonate; (2) The nickel source comprises nickel acetate and / or nickel acetylacetonate; (3) The organic solvent includes benzyl alcohol; (4) The chelating agent includes 1,3-propylene glycol; (5) The molar ratio of the manganese source to the nickel source is (0.5-2):1; (6) In the first mixed system, the concentration of the manganese source is 50 to 150 mmol / L, and the concentration of the nickel source is 50 to 150 mmol / L; (7) The volume ratio of the organic solvent to the chelating agent is (4-19):1; (8) The method for preparing the first mixed system specifically comprises: mixing a manganese source, a nickel source, an organic solvent and a chelating agent and stirring for 10 to 20 minutes.

5. The method for preparing a composite positive electrode material according to claim 3, characterized in that: In the second mixed system, the concentration of the carbon nanotubes is 1 to 4 mg / mL.

6. The method for preparing a composite positive electrode material according to claim 3, characterized in that: Contains at least one of the following features (1) to (2): (1) The temperature of the microwave heat treatment is 150 to 210° C., and the time of the microwave heat treatment is 5 to 40 minutes; (2) During the microwave heat treatment, the second mixed system is stirred at a speed of 300 to 900 rpm.

7. The method for preparing a composite positive electrode material according to claim 3, characterized in that: Contains at least one of the following features (1) to (3): (1) The calcination temperature is 160 to 240° C. and the calcination time is 1 to 3 hours; (2) The atmosphere of the calcination treatment is a protective gas; (3) Before the calcination treatment, the solid matter is dried at a temperature of 60 to 90° C. for a time of 5 to 10 hours.

8. A positive electrode sheet, characterized in that: The invention comprises the composite positive electrode material described in claim 1 or 2, or a composite positive electrode material prepared by the preparation method of the composite positive electrode material described in claims 3 to 7.

9. A battery, characterized in that: A positive electrode sheet comprising the positive electrode sheet according to claim 8.

10. An electrical device, characterized in that: A battery comprising the battery of claim 9.

Citation Information

Patent Citations

  • Positive electrode active material for secondary battery and magnesium secondary battery using the same

    CN102544467A

  • Core-shell NiO / C porous composite lithium ion battery negative electrode material

    CN106711419A

  • Preparation method and application of amorphous transition metal oxide packaged manganese-based oxide composite material

    CN113371759A

  • Nanotube-shaped lithium manganese silicate composite positive electrode material, preparation method, positive plate and battery

    CN116022800A

  • Method for preparing loading type NiB non-crystalline alloy catalyst with the aid of microwave

    CN1792439A